Effect Analysis of Protein Intake of Pedicab Driver in Surabaya - Amelia Lorensia; Rivan Virlando Suryadinata; Bela C. M. Sidabutar (Journal of Tropical Pharmacy and Chemistry, 2021)
Approximately 64 million people suffer from copd and 3 million people die from copd. No exception to pedicab rickshaw drivers, which is one job that has a high risk of copd. From workplace factors that are always exposed to vehicle fumes and dust pollution and also lifestyles such as smoking habits. Pedal rickshaw drivers are also classified as low economic groups, so their daily food intake is sometimes insufficient. Thus making daily protein intake also reduced, protein intake is very important in copd disease. Where protein can improve the performance of respiratory muscles and improve immune function. This study uses a 24-hour recall method by recording the respondent's food history in the last 24 hours to see how daily food protein intake. In this study lung function measurements were also performed using spirometry where the normal value is if fev1 / fvc> 70%. Obtained a total of 124 respondents with a total of 62 in the lung function disorder group and 62 non-impaired groups of respondents aged an average of 55-64 years with a history of working as a pedicab driver for approximately 5 years. In the different test the asymp sig has a result of 0.000 where the conclusions in this study are as follows: there is a significant difference between daily food protein intake in the pedicab rickshaw driver group with impaired pulmonary function and non pedestrian pedicab driver.